The Scandinavian baltic pancreatic club (SBPC) database: design, rationale and characterisation of the study cohort. (3rd August 2017) - Olesen, Søren S.; Poulsen, Jakob L.; Drewes, Asbjørn M.; Frøkjær, Jens B.; Laukkarinen, Johanna; Parhiala, Mikael; Rix, Iben; Novovic, Srdan; Lindkvist, Björn; Bexander, Louise; Dimcevski, Georg; Engjom, Trond; et al.
Abstract: Objectives: Chronic pancreatitis (CP) is a multifaceted disease associated with several risk factors and a complex clinical presentation. We established the Scandinavian Baltic Pancreatic Club (SBPC) Database to characterise and study the natural history of CP in a Northern European cohort. Here, we describe the design of the database and characteristics of the study cohort. Methods: Nine centres from six different countries in the Scandinavian-Baltic region joined the database. Patients with definitive or probable CP (M-ANNHEIM diagnostic criteria) were included. Standardised case report forms were used to collect several assessment variables including disease aetiology, duration of CP, preceding acute pancreatitis, as well as symptoms, complications, and treatments. The clinical stage of CP was characterised according to M-ANNNHEIM. Yearly follow-up is planned for all patients. Results: The study cohort comprised of 910 patients (608 men: 302 women; median age 58 (IQR: 48–67) years with definite 848 (93%) or probable CP 62 (7%). Nicotine (70%) and alcohol (59%) were the most frequent aetiologies and seen in combination in 44% of patients. A history of recurrent acute pancreatitis was seen in 49% prior to the development of CP. Pain (69%) and exocrine pancreatic insufficiency (68%) were the most common complications followed by diabetes (43%). Most patients (30%) were classified as clinical stage II (symptomatic CP with exocrine or endocrine insufficiency). Less than 10% of the patients had undergone pancreatic surgery. Conclusion: The SBPC database provides a mean for future prospective, observational studies of CP in the Northern European continent.